ACADEMIC DISCIPLINES IN ARISTOPHANES' CLOUDS (200-3) - BROMBERG, JACQUES A. (Classical quarterly, 2012)
[...]various fifth-century texts do take up the question of what constitutes a techn and do attempt to systematize and teach a body of scientific knowledge. [...]my goal is not to position Aristophanes as the first to conceptualize or articulate disciplines in the ways he does, nor to argue that his notions of academic disciplines differ materially from those of his contemporaries. [...]Dennistons investigation of technical terms in Aristophanes opens with precisely this observation: [...]writes Miller, Aristophanes transmutes these words and uses them for his own purpose.13 The subject of his paper, and of Dennistons, is not comic coinages, but rather comic uses of acknowledged and attested technical terms. Aristophanes is certainly no stranger to speaking technical nonsense, and it is perhaps no coincidence that the author of On Ancient Medicine parodies a weakness in traditional medicine by imagining in dialogue form this brief, absurd exchange between a doctor and a patient.19 The second useful characteristic of a discipline that I will suggest is implied by Platos critique (in Timaeus 91d, for instance, and Republic 7.52931) of many natural scientists, who rely too closely on their senses for conducting empirical research a criticism levelled also by earlier Presocratic thinkers.20 On this point, Dicks and Neugebauer have denied the existence of scientific astronomy before about 430 B.C., emphasizing mathematical precision in addition to empirical observation as essential features.21 Kahn has challenged this history by observing the mathematical underpinnings of Presocratic astronomy: